Application Study of Art Deco Style to Buildings at Teluk Betung, Bandar Lampung - Fadilasari, Dewi; Ergantara, Rani Ismiarti; Al-Zena, Rafa (Universitas Bandar Lampung (UBL), 2025)
Teluk Betung was the capital of Lampung residency during the Dutch colonial era and has historical value. There were colonial-style buildings, including art-deco. Therefore, it is necessary to conduct a study on “The Application of Art deco Style in Teluk Betung”. This research was qualitative, with historical methodology. The research area determined based on previous studies, then defining the art-deco style buildings. There were 11 art-deco style buildings. Precedents were taken from art-deco style buildings on Braga Street, Bandung. The findings of this study were: (a) The use of art deco ornamentations in Teluk Betung was minimal, unlike in Braga, which was rich, detailed and heavy; (b) art-deco in Teluk Betung used flat, 2-dimensional geometric square elements, while in Braga, the decorative elements were 3-dimensional and protruding; (c) most of corner buildings had segmented and rigid turns, only a few having streamlined, curved corners. In Braga, most corner buildings had streamlined turns; (d) horizontal-line elements stood out in the art-deco buildings in Teluk Betung, meanwhile in Braga, horizontal lines were not as prominent as they were. Overall, the art deco characteristics in the Teluk Betung were geometric deco, horizontal straight-line deco, streamlined deco, and a few ornamental deco elements.